Karakteristik dan Motivasi Petani Pengembang Urban Farming di Kota Surabaya - Baik, Stevi Putri Adolvina; Nurhadi, Eko; Yuliati, Nuriah (Universitas Galuh, 2024)
Urban farmers are one of the milestones in the success of urban farming. Farmer behavior that can be observed is the farmer's characteristics and motivation which are reflected in the farmer's goals and reasons for carrying out urban farming. The research aims to analyze the characteristics of urban farming farmers in the City of Surabaya and identify the goals and reasons for farmers carrying out urban farming. The research was carried out on 5 Women Farmer Groups (KWT) and Farmer Groups (Poktan) in the City of Surabaya, namely, the Guyub Rukun Women Farmer Group, the Farmer Group Yurga Farm, Serpis Farming Group, Sri Rejeki Jitu Farming Group, and Dorang Cinta Farming Women's Group. The first objective analysis uses descriptive tables, and the second objective uses quantitative analysis with the CFA (Confirmatory Factor Analysis) analysis tool. The results of the research are that there are diverse characteristics of each farmer. The majority of Guyub Rukun KWTs are aged over 61 - 65 years, while in other KWTs and Poktans the majority are aged 41 - 45 years so that urban farming can be carried out by anyone. At the education level, farmers have the courage to innovate and are supported by the number of family responsibilities and the farmer's employment status which encourage them to carry out urban farming. Farmer motivation is based on 7 goals in urban farming, namely psychological health and well-being, environmental ecology, food security, environmental friendliness, economics, economic stimulus, and urban revitalization. aimed..